(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s
(3ChdgG (B:s
(3HGH GdMGA hGdSjf hGdHGA s
(3BNQgG (B:s
(3HGH GdNeGSi ef GdNGA s
(3Ydjg NW jGbhf Hf YHOGddg GdQheis
(3bhHd gPG GdLRA Ydi fSNI efbhdI ef NW GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311s
Keywords: (3GddZIs